Computational program for the 3D simulation of the indoor temperature distribution - Dopazo, José; Almao, Nastia; Rincón, José (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
This work presents the development of a computational program called EVITA 3D written in Fortran 77, for the simulation of the indoor temperature distribution. The program solves the unsteady form of continuity, momentum and energy equations using a Piso-like scheme on a non-staggered grid and with a bounded high order treatment for the convection terms. The 3-D physical domain is divided into several zones to include the different materials of the building (e.g. walls, floor, ceiling). The energy equation is solved using transient boundary conditions such as outdoor temperature, horizontal and vertical surfaces global solar radiation, long wave radioactive exchange between external surfaces and sky, floor temperature and mean wind velocity. The movement of air inside the building is simulated using the Boussinesq approach. EVITA 3D results were compared with experimental data, showing good agreement.